MENGATASI BODY DISSATISFACTION PADA WANITA DEWASA AWAL MELALUI KONSELING REALITA DI KABUPATEN KUDUS - Hidayati, Siti Noor; Sumarwiyah, Sumarwiyah; Lestari, Indah (Universitas Muria Kudus, 2023)
The research objectives in this study are: (1) To find the factors that influence Body Dissatisfaction in early adult women. (2) Helping to overcome Body Dissatisfaction through Reality counseling . Body dissatisfaction is a negative evaluation of the body that occurs because of the difference in body size and shape that you currently have with other people's body sizes and shapes that are more ideal. Indirectly, many women are dissatisfied with the shape and size of their bodies caused by physical changes at every stage of development and the prevailing beauty standards. Reality Counseling is a form of practical, relatively simple help relationship and a form of direct assistance to the counselee that the counselor can do in order to develop and foster the counselee's personality/mental health. The process of providing assistance is carried out by giving responsibility to the counselee concerned. Body dissatisfaction is a negative evaluation of the body that occurs because of the difference in body size and shape that you currently have with other people's body sizes and shapes that are more ideal. Indirectly, many women are dissatisfied with the shape and size of their bodies caused by physical changes at every stage of development and the prevailing beauty standards This research was conducted in the Kudus area. The research approach used is a qualitative case study. The research subjects or counselees are NP and AK. Data collection techniques using observation, interviews and home visits. Analysis of the data used is the bacon system. The results showed that the internal body dissatisfaction factors for counselee I (NP) were: biological and physical. The external factors are: body comparison. Counsel II (AK) on the internal factors that cause body dissatisfaction, namely: individual psychological and cognitive characteristics. While external factors are: exposure to social media and film shows. After giving Reality counseling, the counselee I and counselee II can be more confident with their appearance and physical form, do not compare their physique with others, and evaluate their body shape positively